Manejo clínico del sindrome de Stevens Johnson - Arias Rojas, Arnulfo; Martínez, Támara (Revista Estomatología, 1995)
Stevens- Johnson syndromeis a selflimit skaness, it snows severa! complication that in some cases carrier the dead. Severa! injures in diferents parts of the body are presents blot blisper and Crups healing. The best way to the teatment is get the superinfection control. Now, we report an especial case that we atended in San Juan de Dios hospital in Cali city; after four days( 4) presented infection conjunctive, whitish secretion in the bag eyepiece, later handled by internal medicine service doctors with the odontology last year students colaboration, that cross by the hospital área. Treatment was effective, the patient became best and be continuend in out hospital servides.